ANALISIS STRATEGI BERSAING USAHA MINUMAN THAI TEA MELALUI PENDEKATAN LIMA KEKUATAN PORTER (STUDI KASUS PADA USAHA PEDAGANG KAKI LIMA MUMTAAZ THAI TEA, BUKIT MERAPIN, PANGKALPINANG) - Debora, Kenni; Ruben Manullang, Rizal; Ahmad Agin, Arka’a (Jurnal Progresif Manajemen Bisnis, 2019)
Purpose of this research is to know what kind of competitive strategy that should be used for MumTaaz Thai Tea have on facing the beverage industry competition. Type of research descriptive with qualitative approach. Type of data that is used in this research is primary data which is owner and secondary data that are document, literature, internet, journal and ect. Data collection technique that is used are observation, interview, documentation, and literature. Processing and analyzing data using descriptive analysis that’s do for identifying competitive strategy by using five forces porter at MumTaaz Thai Tea. Result of this research shows by MumTaaz Thai Tea were in the position of quadrant I (one) that is anaggressive and strategy that isi right for this position is the growth oriented strategy (Growth Oriented Strategy). So the alternative strategy that is suiteable for the business development of MumTaaz Thai Tea is by using SWOT matrix is strategy S-O (Strenght-Opportunities). Strategy that should be used is minimize of the internal problems and maximine the ultilization of opportunities in the confront of existing threats.